Principals' Transformational Learning Leadership in Digital Lifestyles and Teachers' Digital-Based Learning - Tusmiarifudin; Syamsul Hadi; Widiyanti (Universitas Pendidikan Ganesha, 2024)
Combining the two concepts of learning and transformational leadership into one new leadership concept is believed to make schools run more effectively. The effectiveness of teachers' digital lifestyles and digital-based learning will be studied in more detail. This research examines how transformational leadership influences teachers' digital-based learning with digital lifestyle as a mediator variable. This type of research is survey research. This research design uses a correlational research study. The population of this research was 197 teachers. The sample for this research was 137 teachers. The data collection method is in the form of a questionnaire or questionnaire. The data analysis technique uses inferential statistical analysis. The research findings show that the principal's transformational learning leadership significantly influences teachers' digital lifestyles. Second, the principal's transformational learning leadership significantly influences teachers' digital-based learning. Third, the teacher's digital lifestyle significantly influences digital-based learning. Fourth, transformational learning leadership and leaders-based learning with the teacher's digital lifestyle as a mediator. It is concluded that transformational learning leadership influences digital lifestyles.